Parents' Perspectives on Guided Parent-Delivered Cognitive Behavioral Therapy for Childhood Anxiety Disorders: A Qualitative Study. (September 2022) - Allard, Charlotte; Thirlwall, Kerstin; Cooper, Peter; Brown, Alex; O'Brien, Doireann; Creswell, Cathy
Cognitive behavioral therapy (CBT) is an effective treatment for child anxiety disorders. Low-intensity forms of CBT, such as guided parent-delivered CBT (GPD-CBT), have been developed to increase access; however, it is unclear why some children benefit from this treatment and others do not. This qualitative study aimed to increase understanding of parents' experiences of GPD-CBT and what facilitates and creates barriers to good outcomes. The sample was derived from a sample of families who took part in long-term follow-up assessments (reported in). Data were analyzed using thematic analysis. Two themes containing five subthemes were developed from the data. Theme 1 described factors influencing the experience of GPD-CBT. Theme 2 described perceived outcomes in the child and wider changes within the family. The identification of facilitators and barriers to the success of GPD-CBT could inform and improve future treatment delivery.